Gravity column chromatography of n-hexane fraction of Rhizophora mucronata leaves from West Nusa Tenggara and their antioxidant activity - Lina Permatasari; Handa Muliasari; Qori'atul Hafizah; Annisa Rizka Nirmala; Hilkatul Ilmi (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2025)
In the last few decades, many diseases have been caused by Radical Oxidative Stress (ROS) or free radicals. Compounds that act as natural antioxidants have been widely developed to counteract these free radicals. Rhizpora mucronata was a mangrove species reported to possess strong antioxidant activity. However, the research is limited to extracts; fractions with more specific compound components have not been explored. The n-hexane fraction of R. mucronata leaves was reported to have high total flavonoid content (TFC). The TFC has a positive correlation with antioxidant activity. Therefore, this study aimed to simplify the compound components in the n-hexane fraction of R. mucronata leaves using gravity column chromatography (GCG) and determine their antioxidant activity. The n-hexane fraction was fractionated using GCG with increasing solvent polarity (n-hexane, chloroform, ethyl acetate, and methanol). The fractions were tested for antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) methods. The fractionation using GCG resulted in 80 fractions. These fractions were grouped based on their thin-layer chromatography (TLC) profiles, resulting in 12 groups of fractions (A-L). Fractions D, F, G, H, J, K, and L, the fractions with enough yield, determined their antioxidant activity using the DPPH and ABTS methods. Fractions D and J tested by the DPPH method had IC50 values of 28.68 ± 1.58 ppm and 9.59 ± 0.39 ppm, respectively. Meanwhile, fractions D and J tested by the ABTS method had IC50 values of 15.10 ± 1.00 ppm and 3.16 ± 0.55 ppm, respectively. Meanwhile, fractions F, G, H, K, and L exhibit antioxidant activity with IC50 values greater than 100 ppm. Fractions D and J have potent antioxidant activity, and both were tested using DPPH and ABTS methods. Therefore, fractions D and J can be further developed as natural antioxidants.